HARUN NASUTION'S ISLAMIC THEOLOGY - Rika Nur Rahma, (Aqidah-Ta: Jurnal Ilmu Aqidah, 2023)
This article aims to explain theology in Harun Nasution's view. This study is important because it sees Muslims in Indonesia still not free from ideological conflicts between sects. Harun's theological thinking is relevant to be applied and introduced, especially in Indonesia so that people who are still bound by the knowledge of one view of understanding theology can broaden their horizons so that in religion they are not rigid and think narrowly. This study uses qualitative research with data collection techniques, namely literature, and uses a sociological approach. The results show that Harun Hasution's thoughts on the concept of absolute freedom and God's will are more similar to the understanding of the Mu'tazilite theology. For God's justice, Harun Nasution prefers to compare and describe several Islamic theological schools of thought without taking sides. In understanding destiny and sunnatullah Harun emphasizes using reason because this will affect the productive nature of the people which will have an impact on the development and progress of Muslims. Mysticism or Sufism in Harun's view is considered neo-sufism. Islamic rational theology can be applied in the midst of the lives of Muslims in Indonesia, especially since there are still many Muslims who only know God's free will. So that the nature and productive level of society will increase so that it can create a peaceful social life and bring society to progress.